Modulation of the Akt Pathway Reveals a Novel Link with PERK/eIF2α, which Is Relevant during Hypoxia - Blaustein, M. (2013)
The unfolded protein response (UPR) and the Akt signaling pathway share several regulatory functions and have the capacity to determine cell outcome under specific conditions. However, both pathways have largely been studied independently. Here, we asked whether the Akt pathway regulates the UPR. To this end, we used a series of chemical compounds that modulate PI3K/Akt pathway and monitored the activity of the three UPR branches: PERK, IRE1 and ATF6. The antiproliferative and antiviral drug Akt-IV strongly and persistently activated all three branches of the UPR. We present evidence that activation of PERK/eIF2α requires Akt and that PERK is a direct Akt target. Chemical activation of this novel Akt/PERK pathway by Akt-IV leads to cell death, which was largely dependent on the presence of PERK and IRE1. Finally, we show that hypoxia-induced activation of eIF2α requires Akt, providing a physiologically relevant condition for the interaction between Akt and the PERK branch of the UPR. These data suggest the UPR and the Akt pathway signal to one another as a means of controlling cell fate. © 2013 Blaustein et al.